2019
DOI: 10.1038/s41598-019-44389-8
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent parathyroid hormone 1–34 induces oxidation and deterioration of mineral and collagen quality in newly formed mandibular bone

Abstract: Intermittent parathyroid hormone (PTH) administration is known to promote bone healing after surgical procedures. However, the mechanism and influence of PTH on the mineral and collagen quality of the jaw are not well understood. Most studies have focused on analyzing the bone density and microstructure of the mandible, and have insufficiently investigated its mineral and collagen quality. Oxidative stress activates osteoclasts, produces advanced glycation end products, and worsens mineral and collagen quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(57 reference statements)
0
4
1
1
Order By: Relevance
“…network that is important for handling mechanical loads such as masticatory and parafunctional loads around implants. Conversely, it was recently reported that intermittent human PTH(1e34) administration worsened bone quality as assessed by collagen integrity in mandibular regenerative bone but not in long bones [42]. Therefore, caution is required in interpreting our results that intermittent injection of PTH improves bone quality based on collagen and bone cells.…”
Section: Discussioncontrasting
confidence: 56%
“…network that is important for handling mechanical loads such as masticatory and parafunctional loads around implants. Conversely, it was recently reported that intermittent human PTH(1e34) administration worsened bone quality as assessed by collagen integrity in mandibular regenerative bone but not in long bones [42]. Therefore, caution is required in interpreting our results that intermittent injection of PTH improves bone quality based on collagen and bone cells.…”
Section: Discussioncontrasting
confidence: 56%
“…The 1–34 amino acid fragment of PTH, i.e., PTH(1–34), is the active sequence responsible for the bone remodeling function of PTH and has been approved for use in the clinical treatment of osteoporosis or as a topical drug in the treatment of bone defects [ 24 ]. Low-dose and intermittent administration of PTH(1–34) leads to anabolic effects in bone regeneration and improvement of bone mineral density [ [25] , [26] , [27] ]. Recently, growing studies have demonstrated that systemic used or local delivery of PTH(1–34) to promote bone regeneration in bone defects [ [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%
“…U slučaju visokih nivoa PTH, povećanje osteoklastne aktivnosti 13 dovodi do poremećaja ravnoteže sistema u pravcu resorpciji kostiju. Osim toga, visoki nivoi PTH mogu smanjiti mineralizaciju i pogoršati kvalitet minerala i kolagena u novoformiranoj kosti 14 . Dakle, ako kortikalna kost gubi debljinu usled bolesti i trabekularna kost se formira slabije mineralizovana, onda to može ugroziti osteointegraciju potpornog implantata.…”
Section: Discussionunclassified
“…In the case of high PTH levels, an increase in osteoclastic activity 13 unbalances the system towards bone resorption. In addition, high PTH levels can reduce mineralization and worsen mineral and collagen quality in a newly formed bone 14 . Therefore, if the cortical bone is losing thickness because of the disease and trabecular bone is formed preferentially but not being substantially mineralized, then supportive implant osseointegration may be compromised.…”
Section: Discussionmentioning
confidence: 99%